Can industrial digitalization promote regional green technology innovation? - Xiaoli Hao; Yi Liang; Cunyi Yang; Haitao Wu; Yu Hao (Journal of Innovation & Knowledge (JIK), 2024)
Regional green technology innovation (RGTI) carries ecological and technological externalities, serving as a crucial force in aligning economic development with the imperative of environmental preservation. Industrial digitalization (indig) exhibits innovative, quality-enhancing, and efficiency-enhancing traits. Yet, the exact effects of indig on RGTI have not been extensively studied. In this study, based on provincial data from 2013-2019 in China, we investigated the linear and nonlinear relationships, spatial characteristics and underlying mechanisms between indig and RGTI through a Hansen threshold model and a mediating effect model. The results showed that: i. indig fluctuates while RGTI increases steadily, both displaying evident spatial agglomeration traits and a unipolar characteristic of regional heterogeneity; ii. indig has effectively boosted RGTI at both national and regional levels, with the exception of the northeastern region; iii. There was a single threshold for industrial digitalization and the positive driving trend exhibited a 'marginally increasing' characteristic; iv. Two critical elements, namely industrial structure advancement and marketization, have partial intermediary roles. Basing on these results, this study presents several policy recommendations.
Keywords: O13; O15; P28; 650; Industrial digitization; green technology innovation; spatial agglomeration; intermediary model; threshold effect; regional heterogeneity